System to optimize the process of booking medical appointments for people with upper extremity disabilities - Monrroy, Gino P. (2024)
People with upper extremity disabilities often face significant challenges when attempting to book medical appointments through conventional online booking systems. These barriers can hinder their ability to access essential healthcare services in a timely manner. To address this problem, this research focuses on the development of an innovative medical appointment booking system that uses voice interaction, complemented by a chatbot interface, to improve the user experience for people with upper extremity disabilities. As a result, a marked improvement in medical appointment booking times was achieved, increasing satisfaction and compliance levels among all users.